Separation of <6 mm oil shale using a compound dry separator. Issue 9 (13th June 2017) - Yu, Xiaodong; Luo, Zhenfu; Li, Haibin; Yang, Xuliang
ABSTRACT: A large amount of fine granular materials (<6 mm) are produced during the mining of oil shale. The combustion characteristics of oil shale improve with decreasing size of these materials, for which reason fine-grain oil shale has a high utility value. However, fine oil shale also contains a significant amount of inorganic mineral impurities which can be reduced by physical separation to improve the oil quality. Based on an analysis of the physical properties of oil shale, this paper proposes a compound dry separation process for the cleaning of <6 mm oil shale grains. The effects of the vibration intensity, air velocity, and back angle of the employed separator on the separation results and oil content of the cleaned oil shale were systematically analyzed. Under the optimal vibrational conditions defined by a vibration intensity of 25.76 (amplitude = 4.0 mm, frequency = 40 Hz), air velocity of 0.66 m/s, and back angle of 45°, the yield comprised 35.8% concentrate and 64.2% tailings, with corresponding oil contents of 10.02% and 0.85%, respectively. The probable error of the highest intensity of segregation achieved was 0.155. The proposed compound dry separation of oil shale particles of up to 6 mm was found to be more efficient compared with conventional methods, and the separated fine grade material can be comprehensively utilized by further pyrolysis treatment.